2016
DOI: 10.1111/bij.12779
|View full text |Cite
|
Sign up to set email alerts
|

Microanatomical diversity of amniote ribs: an exploratory quantitative study

Abstract: Bone microanatomical diversity in extant and extinct tetrapods has been studied extensively, using increasingly sophisticated quantitative methods to assess its ecological, biomechanical and phylogenetic significance. Most studies have been conducted on the appendicular skeleton, and a strong relationship was found between limb bone microanatomy and habitat preferences. Few comparative studies have focused on the microanatomy of the axial skeleton and its ecological signal. In the present study, we propose the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 87 publications
4
36
0
Order By: Relevance
“…The proximal rib sample reveals a reduction in growth rate, indicated by a closer spacing of LAGs after LAG 6. The comparison of the rib of Batrachotomus with several modern taxa (lepidosaurs, archosaurs, and mammals) supports the results of Canoville et al (2016) that rib microstructure is largely related to body size (and to a lesser amount to life style), because Batrachotomus shares with most larger taxa the presence of a spongiosa surrounded by a ring of compact cortex (Canoville et al, 2016).…”
Section: Discussionsupporting
confidence: 65%
“…The proximal rib sample reveals a reduction in growth rate, indicated by a closer spacing of LAGs after LAG 6. The comparison of the rib of Batrachotomus with several modern taxa (lepidosaurs, archosaurs, and mammals) supports the results of Canoville et al (2016) that rib microstructure is largely related to body size (and to a lesser amount to life style), because Batrachotomus shares with most larger taxa the presence of a spongiosa surrounded by a ring of compact cortex (Canoville et al, 2016).…”
Section: Discussionsupporting
confidence: 65%
“…The observed histological variability reflects differences in sampling location along the rib shaft as well as taxonomical differences and different anatomical positions and thus function of the ribs in the trunk region (e.g., presence of fibers). A correlation of the development of the spongiosa in the medullary region with size as Canoville et al () found was not documented for Triassic Sauropterygia.…”
Section: Discussionmentioning
confidence: 89%
“…Rib microanatomy was in the focus of a few studies (e.g., de Buffrénil and Mazin, ; de Buffrénil et al, ; Amson et al, ;Houssaye et al, ; Canoville et al, ) but comparison is often difficult due to the lack of a homologous sampling location along the ribs and between ribs along the ribcage (Houssaye et al, ). Canoville et al () were the first who provided an overview of rib inner organization conducted on a large sample of extant amniotes from which standardized midshaft sections of middorsal ribs were taken. They found that ribs exhibit an ecological signal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quantifying and categorizing behavioural ecology is difficult, particularly in such broadly defined regimens as habitat (Al-Kahtani et al, 2004;Gartner et al, 2010;Canoville et al, 2016). Like many other animals, snakes rarely reside in exclusively one type of habitat, although notable exceptions include the viviparous sea snakes and blind snakes (Scolecophidia).…”
Section: Muscle Length Vertebral Number Constriction Sidewinding Amentioning
confidence: 99%